Gender Representation in English Textbooks for Nusantara Kids: A Critical Discourse Analysis Study - Indah Pesona Aisyah; Radinda Rosaria Ramdani; Salma Fathiyah Rahadatul Aisyi; Hapid Ali (Jurnal Langua, 2026)
This study investigates gender representation in the English textbook "Nusantara Kids for Grade 5 SD/MI," officially published by Indonesia's Ministry of Education, Culture, Research, and Technology under the Merdeka Curriculum. Employing Fairclough’s (1995) Critical Discourse Analysis (CDA) framework, this qualitative research examines character frequency, assigned roles, specific character traits, and embedded ideological messages in the textbook's texts, dialogues, and illustrations. The findings reveal a consistent male-centered pattern. Male characters appear more frequently (58%) than female characters (37%). Furthermore, male characters are predominantly assigned professional and public roles, such as doctors or community leaders, while female characters are overwhelmingly confined to domestic tasks like cooking and childcare. Regarding character traits, males are depicted with competence, agency, and leadership, whereas females are attributed nurturing qualities like patience and kindness. Consequently, the textbook's ideological messages normalize male centrality and authority, positioning women in supportive or peripheral roles. Although minor attempts at gender balance exist, they fail to overcome the prevailing male dominance. These subtle representational patterns reinforce patriarchal norms, critically impacting young learners during their formative gender identity development. Finally, this study explicitly recommends that textbook developers, policymakers, and educators adopt more inclusive practices to foster gender-equitable English language education in Indonesia